Cardiovascular risk in patients with selected cutaneous diseases - Gorajek, Anna; Mikut, Karolina; Maj, Dominik; Wieteska, Małgorzata (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Cardiovascular diseases (CVD) are the leading cause of death worldwide. The classic cardiovascular risk factors include age, gender, obesity, diabetes, hypertension, dyslipidemia, smoking and genetic factors. Some dermatological disorders are also potential risk factors for the development of CVD. The aim of the study is to review recent knowledge on the impact of dermatological diseases on cardiovascular risk. Description of the state of knowledge: The relationship between skin diseases and cardiovascular risk is influenced by various common dependencies such as: shared pathophysiological basis of disorders, risk factors, presence of a chronic inflammatory process, genetic susceptibility and environmental influences. Increased cardiovascular risk has been reported for several dermatological conditions, including psoriasis, systemic lupus erythematosus, systemic sclerosis, pemphigus, hidradenitis suppurativa, rosacea, atopic dermatitis. Chronic systemic inflammation, typically present in skin conditions, is a cardiovascular risk factor, because inflammation accelerates atherosclerosis, and furthermore may predispose patients to the development of metabolic syndrome, insulin resistance and diabetes mellitus. In patients who are initially metabolically unbalanced, these processes may be even more intense. Cardiovascular disorders, the frequency of which increases in patients with skin diseases, include atherosclerosis, coronary artery disease, ischemic heart disease, cardiac dysfunction, arrhythmias, heart failure, cerebrovascular disease (stroke, TIA) and peripheral arterial disease. Summary: Many cutaneous disorders, in addition to significantly increasing cardiovascular morbidity and mortality, also reduce the patient's quality of life. The cooperation of dermatologists and cardiologists in the care of patients with dermatological diseases is crucial for the proper treatment of the disease and prevention of cardiovascular complications.